More than forty years of nucleic acid structural science. (1st September 2022) - Parkinson, Gary N.; Berman, Helen
Graphical abstract: Abstract: As scientists who have worked with Stephen Neidle over many years and stages of his career, we present our perspective of his contributions to nucleic acid structural science. We trace some of the highlights of his research on nucleic acid drug interactions and the unique insights about the importance of hydration.